Convergence Analysis of an Improved BFGS Method and Its Application in the Muskingum Model. (18th August 2020) - Yang, Tianshan; Li, Pengyuan; Wang, Xiaoliang
Abstract : The BFGS method is one of the most effective quasi-Newton algorithms for minimization-optimization problems. In this paper, an improved BFGS method with a modified weak Wolfe–Powell line search technique is used to solve convex minimization problems and its convergence analysis is established. Seventy-four academic test problems and the Muskingum model are implemented in the numerical experiment. The numerical results show that our algorithm is comparable to the usual BFGS algorithm in terms of the number of iterations and the time consumed, which indicates our algorithm is effective and reliable.